Prion Protein on Human Leukocytes Is Reduced in Iron Deficiency – Possible Implications for Age-related Macular Degeneration?. (3rd August 2021) - Lindner, Ewald; Woltsche, Nora; Merle, David; Steinwender, Gernot; Strohmaier, Heimo; Nairz, Manfred; Ivastinovic, Domagoj
ABSTRACT: Purpose/Aim of the study : Studies in mouse models have suggested a role for the cellular prion protein in iron metabolism of the eye. Here we have investigated whether iron metabolism affects the expression of prion protein in humans. Materials and Methods: Patients presenting to the department of ophthalmology of the Medical University of Graz for reasons unrelated to prion diseases were enrolled. Parameters of iron metabolism, including ferritin and soluble transferrin receptor were measured by routine laboratory tests. Serum prion protein was determined by enzyme-linked immunosorbent assay. Surface prion protein on CD14 + monocytes and CD4 + T cells was analyzed by fluorescence activated cell sorting. Results: 95 patients were enrolled. Soluble transferrin receptor correlated significantly with prion protein levels on CD14 + POM1 + monocytes ( P = .001, r = −0.7) and on CD4 + POM1 + T cells ( P = .01, r = −0.62). Conclusion: Our findings suggest a connection between the physiological function of the prion protein and iron metabolism in humans.